Biomimetic methodology to produce polymeric multilayered particles for biotechnological and biomedical applications - Lima, A. C. (2013)
The production of multi-compartmented particles for biomedical and biotechnological applications is challenging and the existing methods usually involve wet and aggressive conditions that compromise the encapsulation efficiency of bioactive agents and the viability of cells. Biomimetic superhydrophobic surfaces allow construction of concentric multilayered polymeric systems, adding sequential layers where molecules or cells may be separately confined in compartments with high efficiency.